Trust, Integration, and Colonial Legacies - Reibold, Kerstin (Nordlit, 2025)
This article argues that enduring legacies of colonialism undermine successful integration of non-Western immigrants in Western societies and that the currently dominant national identity model does not allow to address these legacies and their effects. The article discusses why trust is an important component of successful integration and identifies and critiques four core features of national identity models. The article then proposes an alternative way to analyze social trust which pays attention to historically grown and international structures that influence the background conditions in which trust relations take place. Such an analysis brings to light a broader picture of what influences trust and successful integration, supplementing the current focus on cultural difference and shared norms with an analysis of prejudice and boundary-making as well as inequality.